Unmasking cryptic biodiversity in polyploids: origin and diversification of Aster amellus aggregate - Mairal, Mario; Šurinová, Mária; Castro, Sílvia; Münzbergová, Zuzana (Annals of botany, 2018)
BACKGROUND AND AIMS: The origin of different cytotypes by autopolyploidy may be an important mechanism in plant diversification. Although cryptic autopolyploids probably comprise the largest fraction of overlooked plant diversity, our knowledge of their origin and evolution is still rather limited. Here we study the presumed autopolyploid aggregate of Aster amellus, which encompasses diploid and hexaploid cytotypes. Although the cytotypes of A. amellus are not morphologically distinguishable, previous studies showed spatial segregation and limited gene flow between them, which could result in different evolutionary trajectories for each cytotype. METHODS: We combine macroevolutionary, microevolutionary and niche modelling tools to disentangle the origin and the demographic history of the cytotypes, using chloroplast and nuclear markers in a dense population sampling in central Europe. KEY RESULTS: Our results revealed a segregation between diploid and hexaploid cytotypes in the nuclear genome, where each cytotype represents a monophyletic lineage probably homogenized by concerted evolution. In contrast, the chloroplast genome showed intermixed connections between the cytotypes, which may correspond to shared ancestral relationships. Phylogeny, demographic analyses and ecological niche modelling supported an ongoing differentiation of the cytotypes, where the hexaploid cytotype is experiencing a demographic expansion and niche differentiation with respect to its diploid relative. CONCLUSIONS: The two cytotypes may be considered as two different lineages at the onset of their evolutionary diversification. Polyploidization led to the occurrence of hexaploids, which expanded and changed their ecological niche.
Keywords: DNA, Chloroplast; Polyploidy; Models, Biological; Phylogeography; Genetic Markers; genetické markery; Evropa; DNA, Ribosomal Spacer; biologická evoluce; Aster; fylogeografie; fylogeneze; DNA chloroplastová; polyploidie; biologické modely; Biological Evolution; Europe; Aster Plant; mezerníky ribozomální DNA; Phylogeny